2006
DOI: 10.1080/17453670610046307
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic proximal bone loss after uncemented hip arthroplasty is related to stem size: DXA measurements in 138 patients followed for 2–7 years

Abstract: Background Periprosthetic bone loss occurs around uncemented femoral stems and may be influenced by the stem size.Patients and methods We studied 138 consecutive patients, 3 (2-7) years on average after a total hip arthroplasty operation (THA) for unilateral osteoarthritis with the Bi-Metric uncemented femoral stem. We analyzed Harris hip score and bone mineral density.Results The mean Harris hip score was 97 at followup. Bone mineral density decreased proximally by 19% in both Gruen zones 1 and 7. Bone loss i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 44 publications
5
58
2
3
Order By: Relevance
“…Before the study, we conducted a power analysis based on data obtained from an earlier study of THA performed using the conventional stem (Sköldenberg et al 2006). In a previous study of hip fracture prevention, a 4.8% increase in BMD in the greater trochanter and a 3.4% increase in BMD in the femoral neck (roughly equivalent to Gruen zones 1 and 7) was associated with a 30% reduction in hip fracture risk (McClung et al 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the study, we conducted a power analysis based on data obtained from an earlier study of THA performed using the conventional stem (Sköldenberg et al 2006). In a previous study of hip fracture prevention, a 4.8% increase in BMD in the greater trochanter and a 3.4% increase in BMD in the femoral neck (roughly equivalent to Gruen zones 1 and 7) was associated with a 30% reduction in hip fracture risk (McClung et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…We therefore assumed that a difference in BMD between our groups of 15% in the proximal zones (roughly 3 times as large as the increase in that study) would also be clinically relevant for our group of osteoarthritis patients, to reduce the incidence of late periprosthetic femoral fractures. A power analysis showed that detection of a 15% difference in BMD at the 5% significance level with a standard deviation of 14% (Sköldenberg et al 2006) would require 17 patients in each group. We did not predefine the use of Bonferroni correction for the primary endpoint.…”
Section: Methodsmentioning
confidence: 99%
“…This can be ascribed to blood-flow disruption due to femoral canal preparation three to six months after surgery [28]. The major BMD decreases in the greater trochanter (R1) and the calcar (R7) are typical for straight stems [3,21,23,25,27,[29][30][31][32]. They occur mostly due to stress shielding in the very proximal portion of the calcar due to the vast proximal cross section of the implant [28,31].…”
Section: Discussionmentioning
confidence: 99%
“…Increase of the stem diameter often necessitated by aging and a thin femoral cortex or reaming of the canal will further promote proximal stress shielding and distal load transfer [42,45]. With smaller stem sizes, the relative stiffness of the stem will become less important, but some studies failed to find any correlation between BMD loss and stem diameter [2,37] or that substantial loss of BMD also occurs with smaller stem sizes [46]. Thus, there might be indications for the use of flexible stems down to size 13, perhaps even smaller, if they can be manufactured without any increased risk of stem breakage.…”
Section: Discussionmentioning
confidence: 99%
“…Use of solid metallic stems fixed without cement has consistently caused proximal bone loss [34,39,40,46]. Increase of the stem diameter often necessitated by aging and a thin femoral cortex or reaming of the canal will further promote proximal stress shielding and distal load transfer [42,45].…”
Section: Discussionmentioning
confidence: 99%